Footwear influences soft-tissue vibrations in rearfoot strike runners (2017)
Muscle activity is tuned in response to ground reaction force to dampen soft-tissue vibrations (Wakeling, Von Tscharner, Nigg, & Stergiou, 2001) during whole-body vibrations (Wakeling, Nigg, & Rozitis, 2002) and running (Boyer & Nigg, 2004). A model study demonstrated this mechanism may be affected by fatigue and shoe hardness (Nikooyan & Zadpoor, 2012). Footwear may then influence soft-tissue vibrations, and thus the part of muscle activity affecting the muscle tuning mechanism.